2013
DOI: 10.1177/1465116513482527
|View full text |Cite
|
Sign up to set email alerts
|

Action and attitudes matter: International public opinion towards the European Union

Abstract: Descriptive studies on the European Union's global image reveal generally favourable feelings towards the European Union on the part of citizens outside Europe. However, European Union perceptions vary considerably across countries. This article argues that these patterns can be analytically explained by taking context and individual factors into account. European Union behaviour and an individual's supranationalist attitude should exert a substantial impact on citizens' feelings. A multi-level model confirms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…() explore the effect of the US President's Emergency Plan for AIDS Relief (PEPFAR) on the popular perception of the United States, demonstrating that the program has improved public opinion of the US in countries benefitting from PEPFAR. In a similar vein, Schlipphak () finds a positive effect of European Union (EU) foreign aid and – to a lesser degree – trade relations on the public image of the EU in recipient countries. In a related study on China's image in Africa, Hanusch () shows that imports from China have had a negative effect on the country's image.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…() explore the effect of the US President's Emergency Plan for AIDS Relief (PEPFAR) on the popular perception of the United States, demonstrating that the program has improved public opinion of the US in countries benefitting from PEPFAR. In a similar vein, Schlipphak () finds a positive effect of European Union (EU) foreign aid and – to a lesser degree – trade relations on the public image of the EU in recipient countries. In a related study on China's image in Africa, Hanusch () shows that imports from China have had a negative effect on the country's image.…”
Section: Introductionmentioning
confidence: 86%
“…Of course, the scholarly literature is sceptical as to whether ODA actually achieves its idealistic goals. Whatever the aggregate long‐term effect of ODA, the extent that foreign aid‐related projects interact with local civil society organizations and contribute to empowerment may lead to the citizens of recipient countries attributing a positive image to the donor country (Schlipphak, ).…”
Section: Introductionmentioning
confidence: 99%
“…The limited literature regarding these questions has, on the elite level, pointed toward the finding that the EU is seen by outside elites as an untrustworthy and unreliable actor, one that only follows its own interests in international negotiations and in its various interventions in domestic politics around the globe (Elgström, ; Scheipers and Sicurelli, , ). In contrast, the existing literature on public attitudes toward the EU has shown that its reputation is quite favourable across the globe, with citizens being largely supportive of the EU as an international organisation (see, for example, Schlipphak, ).…”
Section: Introductionmentioning
confidence: 95%
“…While some studies have looked into the feelings of citizens about regional integration in Africa, East Asia, Southeast Asia and Latin America (Schlipphak, ; Jhee, ), others have turned to global or regional public opinion vis‐à‐vis international organisations such as the UN (Dellmuth and Tallberg, ; Johnson, ), international financial institutions (Edwards, ), or the EU (Chaban et al ., ; Chaban, Elgström and Holland, ; Lucarelli, ; Schlipphak, ). In general, previous research has found the theoretical approaches and empirical findings derived from the American or European contexts to be more or less generalisable to other locations across the globe.…”
Section: What Influences Arab Attitudes Toward the Eu? Theoretical Exmentioning
confidence: 99%
See 1 more Smart Citation